Efektivitas Pengelolaan Keuangan dan Akuntansi Pada Badan Usaha Milik Desa (BUMDes) Dengan Pendekatan Goal Model - Nurhazana Nurhazana; Endang Sri Wahyuni (Politeknik Negeri Bengkalis, 2020)
One form of economic strengthening in the village development with the formation of village-owned business entity (BUMDesa) by utilizing local resources in an effort to improve the welfare of rural communities. Village financial management patterns are different from BUMDesa management, but the two cannot be separated in terms of accountability for the participation of funds. Starting from this BUMDesa in carrying out its business unit activities, BUMDesa funding sources come from the community, loans / grants from the Government both local and central government. Relating to BUMDesa's business activities which are inseparable from various risks. This research is a literature study that aims to see practically how the effectiveness of BUMDesa's financial management and accounting with the goal model approach. Indicators of the effectiveness of BUMDesa with the goal model approach will be seen in meeting the objectives of BUMDes in the form of achieving the final results of the Business Entity and not seen from the way or process the business entity is moving. This does not deny that good financial management must start from the process of planning, implementing, administering , reporting, financial accountability. The important thing in Accounting is the process of recording and reporting on the use of funds collected to be held accountable to the village community.